Prospective observational study on the role of catheter colonization and multidrug-resistance associated with catheter-related bloodstream infections - Pinto, Miguel (2022)
Background: Central venous catheter (CVC)-related bloodstream infection (CRBSI) is a huge public health consern with considerable impact on mortality and health costs. The emergence of antimicrobial resistant microorganisms associated or not with CVC colonization by biofilms makes the treatment of CRBSI even more challeging. Methods:A 3-year observational study enrolling 3 tertiary hospitals located in Lisbon (Portugal) was designed to identify the major etiological agent of 58 CRBSI, their ability to colonize CVCs and their antimicrobial resistance profiles. Etiological agents of CRBSI were idebtified by VITEK-2. Whole-genome sequencing was used to confirm CRBSI by the most prevalent etiological agents and characteriza their resistome. CVC's colonization (namely by biofilm assembly) was monitored by scanning electron microscopy. Results: Staphylococci were the most prevalent causative agent (36/58, 62%), with S. aureus and coagulase negative S. epidermidis accounting for 24.1% and 36.2% of CRBSIs, respectively. Comparative genomic analysis of CVCs/hemoculture pairs of isolates revealed genomic matches for 35/36 pairs and a good correlation between antibiotic susceptibility phenotype and the presence of antimicrobials resistance genetic determinants. CVCs colonization was observed mainly in the catheter lumen and presented different phenotypes ranging from isolated attached microorganisms to mature biofilms. The latest phenotype, mature biofilms of S. epidermidis and S. aureus were found for 50.0% and 48.6% of the CVCs, respectively. Nevertheless, no statistical significant association was established between biofilm assembly and CRBSI highlighting the need for further studies to elucidate biofilms' role on this HAI. Conclusion: WGS proved to be a valuable tool to confirm CRBSI. Despite staphylococci biofilms identification on a considerable number of CVCs, no statistically significant association was found between CRBSI and biofilms.